Dinamika Penutupan Patung Bunda Maria di Yogyakarta - sukron azhari, sukron (Kopertais Wilayah III Yogyakarta, 2023)
Religion plays an important role in the daily life of Indonesians. This is part of one's personal identity, ethnic identity and also one's political identity, as well as the identity of the nation itself. Indonesia is a multi-religious country, with a wealth of religions and beliefs, even though the majority of its people (about 90 percent) claim to be Muslim. This paper discusses the public's response to the Statue of the Virgin Mary at the Sasana Adhi Rasa Prayer House St. Yacobus in the Degolan Hamlet, Bumirejo Village, Lendah, Kulon Progo, Yogyakarta, using the Social Solidarity Theory by Emil Durkheim and the Peacekeeping Theory by Johan Galtung.